2008
DOI: 10.1359/jbmr.071112
|View full text |Cite
|
Sign up to set email alerts
|

Association of Bone Morphogenetic Proteins With Otosclerosis

Abstract: We studied the role of polymorphisms in 13 candidate genes on the risk of otosclerosis in two large independent case-control sets. We found significant association in both populations with BMP2 and BMP4, implicating these two genes in the pathogenesis of this disease.Introduction: Otosclerosis is a progressive disorder of the human temporal bone that leads to conductive hearing loss and in some cases sensorineural or mixed hearing loss. In a few families, it segregates as a monogenic disease with reduced penet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
86
1
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(94 citation statements)
references
References 77 publications
4
86
1
3
Order By: Relevance
“…In mice, an enhancer in the 39 region of BMP2 has been identified that influences expression in osteoblast progenitor cells (Chandler et al 2007), and in humans, SNPs in the 39 region are associated with otosclerosis (Schrauwen et al 2008), a progressive disease of the temporal bone that can lead to hearing loss. Additional bioinformatics analyses of the BMP2 downstream region, and the remaining 100 nongenic regions, may provide valuable insights into distinguishing characteristics of these loci, guide experimental studies, and generate testable evolutionary hypotheses.…”
Section: Regulatory Versus Protein Adaptive Evolutionmentioning
confidence: 99%
“…In mice, an enhancer in the 39 region of BMP2 has been identified that influences expression in osteoblast progenitor cells (Chandler et al 2007), and in humans, SNPs in the 39 region are associated with otosclerosis (Schrauwen et al 2008), a progressive disease of the temporal bone that can lead to hearing loss. Additional bioinformatics analyses of the BMP2 downstream region, and the remaining 100 nongenic regions, may provide valuable insights into distinguishing characteristics of these loci, guide experimental studies, and generate testable evolutionary hypotheses.…”
Section: Regulatory Versus Protein Adaptive Evolutionmentioning
confidence: 99%
“…Several association studies have been performed to determine the genetic contributors for sporadic forms of OTSC. These studies have shown the association of OTSC with polymorphisms in the COL1A1 (MIM 120150), TGFB1 (MIM 190180), BMP2 (MIM 112261), BMP4 (MIM 112262), and RELN (MIM 600514) genes (McKenna et al, 1998;Thys et al, 2007a;Schrauwen et al, 2008;Schrauwen et al, 2009;Khalfallah et al, 2010;Khalfallah et al, 2011;Priyadarshi et al, 2013;Ealy et al, 2014). Some of the studies failed to replicate these associations due to small sample size or different ethnicity (Tshifularo & Joseph, 2008;Priyadarshi et al, 2010;Iossa et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A recent case/control association study has shown that there is a variant of TGFB1 that is underrepresented in patients with otosclerosis as compared to control subjects in Belgian-Dutch and French populations (Thys et al, 2007b). Identification of an association of two bone morphogenetic proteins, BMP2 and BMP4, with otosclerosis lends additional support to a role for TGF-β signaling in the disease process (Schrauwen et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Another more robust study showed that there is an under-representation of an active variant of TGFB1 in otosclerosis patients, which may inhibit osteoclast differentiation and initiation of aberrant bone remodeling in the otic capsule (Thys et al, 2007b). Association of two bone morphogenetic proteins, BMP2 and BMP4, has also been reported (Schrauwen et al, 2007). In aggregate, these data provide compelling evidence that otosclerosis is a genetically heterogeneous disease, although our understanding of the pathways involved remains speculative; the possibility of environmental triggers remains unanswered.…”
Section: Introductionmentioning
confidence: 99%